Implementation of the Entrepreneurship Curriculum with the Deming Cycle at Islamic Senior High School - Fahrudin, Ahmad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to describe and analyze the implementation of an entrepreneurship curriculum based on the PDCA (Plan-Do-Check-Act) cycle at SMA Islam Sunan Gunung Jati Tulungagung. Employing a descriptive qualitative approach with a case study method, data were collected through in-depth interviews with the principal, vice principal for curriculum affairs, entrepreneurship teachers, program coordinators, and students from Grades XI and XII. Additional data were obtained through observation of entrepreneurship learning activities—including classroom teaching, student business projects, and school entrepreneurship events—and document analysis of lesson plans, modules, rubrics, and student business products. The analysis followed Miles and Huberman’s interactive model involving data reduction, data display, and conclusion drawing. The findings show that the curriculum was planned collaboratively and rooted in local potentials. Implementation emphasized experiential, project-based learning integrated with Islamic values and 21st-century skills such as collaboration, creativity, and digital literacy. Evaluation was conducted formatively and reflectively, assessing not only cognitive understanding but also affective aspects like responsibility and honesty. Follow-up activities included mentoring, advanced training, and integration of digital tools to support continuous improvement. The novelty of this study lies in the integration of the PDCA cycle into an entrepreneurship curriculum that aligns with Islamic and multicultural values, making it relevant to the sociocultural realities of students. This research contributes conceptually to the development of contextual, adaptive, and character-based curricula in Islamic education, providing a reference for similar initiatives in other institutions. It demonstrates that entrepreneurship education can serve as a strategic medium for character formation and socio-economic empowerment.